2007
DOI: 10.1128/jvi.01058-07
|View full text |Cite
|
Sign up to set email alerts
|

Even Attenuated Bovine Leukemia Virus Proviruses Can Be Pathogenic in Sheep

Abstract: Based on a reverse genetics approach, we previously reported that bovine leukemia virus (BLV) mutants harboring deletions in the accessory R3 and G4 genes persist at very low proviral loads and are unable to induce leukemia or lymphoma in sheep, indicating that these R3 and G4 gene sequences are required for pathogenesis. We now show that lymphoma can occur, albeit infrequently (1 case of 20) and after extended periods of latency (7 years). Direct sequencing and reinfection experiments demonstrated that lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…These sequences correspond to the third and second exons of R3 and G4, respectively, revealing that these sequences may not be essential for infectivity in vivo. Although previous studies have shown that deletions in R3/G4 interferes with the efficiency of BLV propagation and restricts pathogenesis [14,15,46,49], another study has shown that one out of 20 sheep infected with a R3/G4 mutant developed a lymphoma after 7.5 years of latency, suggesting that the deleted sequences may not be strictly required for pathogenesis [51]. Further studies will be needed to address the biological significance of these findings in studies using the cow as a model for BLV infection.…”
Section: Resultsmentioning
confidence: 99%
“…These sequences correspond to the third and second exons of R3 and G4, respectively, revealing that these sequences may not be essential for infectivity in vivo. Although previous studies have shown that deletions in R3/G4 interferes with the efficiency of BLV propagation and restricts pathogenesis [14,15,46,49], another study has shown that one out of 20 sheep infected with a R3/G4 mutant developed a lymphoma after 7.5 years of latency, suggesting that the deleted sequences may not be strictly required for pathogenesis [51]. Further studies will be needed to address the biological significance of these findings in studies using the cow as a model for BLV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Several laboratory trials showed that Tax could transform cells in in vitro cultures and being oncogenic in animal models where cells can be transformed when Tax is combined with ha-ras oncogene to produce tumor cells in athymic mice and fibroblasts immortalization coming from rat embryo [24,25]; 2) Viral genome integration process close to highly active cellular genome segments associated with cell division [26]. This is how the Avian Sarcoma Leukosis Virus (ASLV) can integrate in many places of cellular genome, but when there is tumor in the host, the virus has been found upstream of the c-myc cellular gene, which codifies for the Myc proteins implicated in the cellular DNA synthesis control [26,27].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Thus, this silent infection is spread worldwide with the exception of Europe, where it has been eradicated (Bartlett et al, 2014). Transmission occurs naturally and iatrogenically through the transfer of infected cells, mainly by blood or milk (Florins et al, 2007). Based on this assumption, the mammary epithelium could play an important role in viral transmission.…”
mentioning
confidence: 99%